The Influence of Digital Literacy and Digital Competence on Employee Work Engagement and its Impact on Coffee Shop Employee Work Performance - Khalifatul Jannah, Vivi; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
This study aims to analyze the influence of digital literacy and digital competence on employee work engagement and its impact on the work performance of coffee shop employees in East Telukjambe, Karawang Regency. The study used a quantitative approach with a sample of 107 employees selected through proportionate stratified random sampling. Data was collected through a Likert scale questionnaire and analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS) with SmartPLS. The results of the study show that digital literacy and digital competence have a significant effect on employee work engagement, digital competence has a significant effect on employee work performance and employee work involvement has a significant effect on employee work performance. However, digital literacy and digital competence do not show a direct influence on employee work performance if through employee work involvement. This research provides advice to coffee shop managers to focus on developing digital literacy and competencies to improve employee work engagement and employee work achievement, which will support business sustainability in a highly competitive industry.